Economic burden of dementia studies in low‐ and middle‐ income countries (LMICs): A systematic review. (31st December 2021) - Mattap, Siti Maisarah; Mohan, Devi; McGrattan, Andrea; Allotey, Pascale; Stephan, Blossom CM; Reidpath, Daniel; Siervo, Mario; Robinson, Louise; Chaiyakunapruk, Nathorn
Abstract: Background: More than two thirds of people with dementia are living in the low‐ and middle‐ income countries (LMICs). The growing dementia prevalence will result in significant economic burden in these countries. This systematic review aimed to summarise the evidence on the economic burden of dementia in LMICs. Method: Seven databases (EconLit, EMBASE, PubMed, Cochrane Review (DARE), ERIC, PsycINFO and CINAHL) were searched from inception to September 2020 for original research articles reporting the economic burden or cost of illness for all‐cause dementia and/or its subtypes e.g., Alzheimer's disease (AD), from any LMICs as defined by the World Bank. Two independent reviewers assessed studies for eligibility. Data on the location, study characteristics, cost estimation methods and estimated costs were extracted. The national level total, direct and indirect costs inflated to 2019, were expressed as a percentage of each country's Gross Domestic Product (GDP) and were summarised using mean percentage of GDP. Study quality was assessed using the Larg and Moss method. Result: The literature search identified 14092 articles, of which 22 studies met the eligibility criteria. The national cost of dementia was reported in 64% of the studies (from 120 countries). The remaining studies reported only patient level cost. Majority of the studies had low risk of bias. The average national dementia cost estimated as proportion of GDP was 0.42%. Informal care or indirect costs on average accounted for 62% of the total cost of dementia, while 38% was due to the direct cost. Conclusion: Dementia is a major cause of economic burden in LMICs. Cost of informal care or indirect cost is the major contributor of this cost. The cost of dementia in LMIC has doubled since first reported in the World Alzheimer Report in 2015 (0.2% of GDP). Acknowledgement: This research was funded by the National Institute for Health Research (NIHR) (16/137/62 ‐ Dementia Prevention and Enhanced Care (DePEC), Newcastle University, United Kingdom), using UK aid from the UK Government to support global health research. The views expressed in this publication are those of the author(s) and not necessarily those of the NIHR or the UK Department of Health and Social Care.